Harmoni Keluarga Beda Agama Di Mlati, Sleman, Yogyakarta - Ermi Suhasti Sy (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
Married couples of different religions argue that they have no serious problems in families. They feel that their couple has fulfilled their needs, they do not live under poverty, and they are happy. In relation to the religious life, they feel that their couple gives much attention on freedom of religion and everyone in their family is free to perform their own religious worship. Their couple never asks them to change their belief to his/her religion. This also occurs in the religious social life in Melati village, Sleman, Yogyakarta. They feel very lucky to live among tolerant society, in which people honor religious diversity. Although they live among tolerant people, they feel uncomfortable in communicating with other people, especially in relation with the religious social activities, because they live in interfaith marriage. This makes them reluctant to be active in religious social activities. This article presents happiness and harmony among couples living in interfaith marriage in Mlati village, Sleman Regency, Yogyakarta.